Matching Is Best: Enhancing Effects of Future Orientation and Construal Level on Green Consumption - Yidi Chen; Qinxin Liu; Shuyu Shan; Cancan Jin (Behavioral Sciences)
The 2024 Report on the Work of the Chinese Government promotes trade in consumer goods and green consumption. Therefore, better understanding is needed of consumer attitudes and behaviors toward environmental protection and sustainable development. The relationships among future orientation, construal level, and green consumption were explored using a delayed-effect design to conduct two surveys at one-month intervals with 160 participants (100 women and 60 men). The results showed that (1) future orientation positively predicted green consumption intention and green consumption behavior, and (2) the construal level significantly moderated the influence of future orientation on green consumption. Specifically, a high construal level and high future orientation predicted the greatest green consumption intention, green consumption behavior, and green consumption decisions, while at a high construal level, future orientation positively predicted green consumption intention and behavior, with a greater tendency to purchase environmentally friendly rather than hedonic products. At a low construal level, future orientation had no significant effect on green consumption intention, behavior, and intention to purchase environmentally friendly products. This study is important for promoting public awareness of the importance of green consumption and encouraging green consumption behaviors to achieve the goals of sustainable development and protect the environment and social well-being.